THE INFLUENCE OF TEACHERS' SKILLS USING ICT AND TEACHER'S TEACHING STYLE ON STUDENTS' LEARNING OUTCOMES OF SMKN 46 JAKARTA USING BLENDED LEARNING - Ardika, Dzikrika Bunga (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to determine the effect of teacher skills in using ICT and teacher teaching styles on student learning outcomes at SMKN 46 Jakarta. The results of this study are: (1) There is a significant positive effect between teachers' skills in using ICT on learning outcomes indicated by the value of t_count 2,846 > t_table 1,98397; (2) There is a significant positive effect between the teacher's teaching style on learning outcomes as indicated by the value of t_count 2,983 > t_table 1,98397; (3) There is a significant positive effect between the skills of teachers in using ICT and the teaching style of teachers on learning outcomes as indicated by the value of nilai f_count 42,2 > f_table 3,09. The multiple correlation coefficient is 0.677 and the coefficient of determination is 0.447 or 58.7%, the variable teacher skills in using ICT and the teacher's teaching style affect student learning outcomes simultaneously and the rest is influenced by other factors studied